Subsequent Entry Biologics in Canada: Current State of the Science - Laszlo Endrenyi; Fakhreddin Jamali; Raimar Loebenberg (Frontiers Media S.A., 2015)
The Canadian Society for Pharmaceutical Sciences organized a workshop on the current state of sciences of subsequent entry biologics (SEBs, biosimilars) on December 10th 2014 in the Health Canada location in Ottawa, ON. The day-long workshop provided an opportunity to discuss recent regulatory developments and a wide range of scientific issues related to SEBs. Following a discussion on the differences between the Canadian guidance and those of other countries,  a series of presentations were made that focused on the regulatory requirements with regard to the product quality, methodology, non-clinical and clinical data. In addition, issues of extrapolation from one indication to another, interchangeability and reimbursement  were articulated. It was also highlighted that both the patients and caregivers need to be better informed regarding the safety and efficacy of articulated SEBs.